TEMPO-Oxidized microcrystalline cellulose for rapid adsorption of ammonium - Ong, Jia Hui (2022)
As low as 1 ppm concentration of ammonia is sufficient to pose a threat to fish cultured in the fish farm, and therefore effective ammonia removal method is necessary to minimize the ammonia concentration. In this study, cellulose, which is one of the low-cost and highly versatile green polymers, has been modified by TEMPO-mediated oxidation and first applied for ammonia removal from water. For the TEMPO-oxidized cellulose of 0.78 mmol/g carboxylate group content, the adsorption capacity was measured to be 8.21 mg/g (empirically, 9.465 mg/g derived from Langmuir isotherm model) from water at pH around 7.0, which is comparable with the existing carbon-based sorbent for the reduction of ammonia. This also indicates close to 100% utilization of the carboxylate adsorption sites. In addition, equilibrium adsorption can be achieved within 5 min. The ammonium adsorption data fit the Langmuir model very well, indicating a monolayer chemical adsorption process. The adsorption performance of the material was minimally influenced by a pH range of 5.0-9.0 but substantially affected by the presence of competing ions. Despite a slight decrease in adsorption performance, the material can be regenerated and applied in a real water sample. Electrostatic interaction and hydrogen bonding between the introduced carboxylate groups and ammonium ions appear to be the adsorption mechanisms governing the material performance in ammonia removal. Further discussion on performance comparison, alternative modification methods, production cost, and potential usage of the postadsorption material is also included.